White Matter Disease and an Incomplete Circle of Willis. Issue 4 (June 2015) - Ryan, Daniel James; Byrne, Susan; Dunne, Ruth; Harmon, Mark; Harbison, Joseph
Introduction: White matter disease occurs as a consequence of small vessel disease; however, hypoperfusion may also play a role. We investigated whether patients with less cerebral vessel anastomosis may develop more white matter disease. Methods: Magnetic resonance imaging (1.5t) with intracranial magnetic resonance angiography data was collected on a convenience sample between July 2008 and January 2009. All patients were independently assessed for circle of Willis variants by two researchers and categorized into two groups: those with a complete circle of Willis and those with an incomplete circle of Willis (absent vessels). The complete group was sub-divided into a classical group (entirely normal circle of Willis) and a hypoplastic group (hypoplasia but no absent vessels). White matter disease assessment was conducted for these groups, by two researchers blind to magnetic resonance angiography findings, on all patients over 50 years old. Results: The circle of Willis was characterized in 163 patients, while 90 (>50 years) underwent white matter disease assessment. The kappa inter-rater reliability between both circle of Willis assessors and between both white matter disease assessors was 0·57 and 0·63, respectively. The prevalence of circle of Willis variants strongly correlated with the seminal paper by Riggs and Rupp. Independent of age and gender, those with an incomplete circle of Willis ( n = 68) exhibited 58% more white matter disease than those with a complete circle of Willis ( n = 22) (white matter disease score 6·52 vs. 4·11, respectively, P = 0·03). Patients with absent anterior vessels exhibited more frontal white matter disease than those with intact anterior vessels (3·7 vs. 1·72, P < 0·001). Patients with absent posterior vessels exhibited more occipital white matter disease than those with intact posterior vessels (2·52 vs. 1·34, P = 0·014). Conclusion: These data suggest that congenital absence of anastomotic capacity correlates with incident white matter disease, thus alluding to a hypoperfusion mechanism in the development of white matter disease.